Current look at effects of long-term proton pump inhibitors therapy - Skrzydło-Radomańska, Barbara (Przewodnik Lekarza/Guide for GPs, 2005)
Introduction of proton pump inhibitors (PPI) provided an important progress in treatment of the acid-related diseases. PPI are largely administered andand frequently used in long-term therapy. Hypergastrinaemia induced by PPI may lead in human to enterochromaffin-like cells hyperplasia. No neoplastic changes have been reported after more than a decade of use. Fat and mineral bioavailability remain unaltered by PPI therapy. However absorption and profound acid suppression for many years may lead to vitamin B 12 deficiency.